The Aural Experience of Laughing and the Sociality of Sound (Re)Production in Communication - Rosyid, Nur; Laksita, Dhimas Unggul (Komunitas, 2018)
This paper explores laugh as an aural and hearing experience in our everyday communication. So far, most of studies understood laugher by its causality explanation and has been paying less attention to the context that laughter is a form of non-verbal and aural experience. We assume that laughter has certain indexicality dimension and social significance to convey meanings and certain sociality in communication. This research tries to develop the method to use audio/ sound in research and how it will be presented in our academic writing and discourses. This study uses ethnographic methods to emphasize the direct subject participation by recording the conversation process. After that, these recordings are transformed into phonography—since this transcription itself is problematic—to understand the intentions and attentions of laughter as well as to decipher the meaning of sound. The results show that laughter has an indexicality dimension to convey implicit meaning. It appears from the intentions of laugh level present(ed) in each specific moment in communication. As we found in some cases, there are different levels of intention to provoke particular attention: audience’s sign to the performer, lessen the formality in a formal meeting, mediating and recalling memory in everyday conversation, and the intention to make friends. Therefore, laugh has different social significances and intentions in everyday interaction and communication. It is not only serve as the sound of liberation or something to make someone feels freer.